China's economic growth engine: The likely types of hardware failure, software failure and power supply failure - Wing Thye Woo (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
The 6th Plenum of the 16th Central Committee of the Communist Party of China (CPC) concluded on October 11, 2006, with the commitment to establish a harmonious society by 2020. The obvious implication from this commitment is that the present major social, economic and political trends are not leading to a harmonious society or, at least, not leading to a harmonious society fast enough. Analytically, if the Chinese economy is depicted as a speeding car, there are three classes of failures (a) a hardware failure from the breakdown of an economic mechanism, a development that is analogous to the collapse of the chassis of the car; (b) a software failure from a flaw in governance that creates frequent widespread social disorders that disrupt production economy-wide and discourage private investment, a situation similar to a car crash that resulted from a fight among the people inside the speeding car; and (c) a power supply failure from hitting either a natural limit or an externally-imposed limit, a situation that is akin, respectively, to the car running out of gas or to the car smashing into a barrier erected by an outsider. For hardware failure we discuss the possible weakening of China's fiscal position generated by the repeated recapitalization of the state banks. For software failure, we discuss possible social disorder caused by outmoded governance. And for power supply failure, we discuss the possible trade disputes from China s chronic trade imbalances and the physical constraints posed by China s rapidly deteriorating natural environment.
URN:NBN:fi:bof-201408071935
Keywords: 330